Ca-Al Layered Double Hydroxides Pillared H4[α-PW12O40]•nH2O as Adsorbent Material for Cadmium (II) Removal from Aqueous Solution - Anggraini, Galuh Kirana; Novitasari, Ade; Amri, Amri (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
Heavy metals in the environment can have a detrimental impact on human health. This study successfully used a new adsorbent material, specifically layered double hydroxide pillared with keggin polyoxometalate H4[α-PW12O40]•nH2O (Ca-Al/POM), to effectively remove cadmium (II) from aqueous solution. The Ca-Al/POM adsorbent has been thoroughly analyzed using X-ray diffraction and FT-IR. The findings showed an increase in the maximum adsorption capacity for cadmium (II) when using Ca-Al LDH intercalated with POM. The study of equilibrium adsorption isotherms showed that the Ca-Al/POM adsorbent effectively removed cadmium (II) and fit the Freundlich isotherm model. In addition, the adsorption kinetics study showed that the adsorption of cadmium (II) on Ca-Al/POM followed a pseudo second-order kinetics model.